2014
DOI: 10.3889/oamjms.2014.043
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Thrombocytopenia in Idiopathic Hyperbilirubinemic Newborns

Abstract: Background: Hyperbilirubinemia is the most common reason for admission during the neonatal period and may develop serious complications. Thrombocytopenia is defined as platelet count <150,000/mm 3 and has not been conclusively reported as a complication of hyperbilirubinemia in any of the standard paediatric textbooks. The aim of this study was to find the incidence of thrombocytopenia in neonates with idiopathic jaundice and the relationship between hyperbilirubinaemia and platelet count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
2
5
1
Order By: Relevance
“…5 In another study conducted 86.4% of neonates had mild thrombocytopenia while moderate and severe thrombocytopenia was seen in 14.6% of babies. 6 Our study didn't observe any significant difference in incidence of thrombocytopenia as far as gender was concerned which is comparable to the study. 5 This study observed that preterm babies who received phototherapy had significantly higher incidence of thrombocytopenia than term babies which was in comparison with the study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…5 In another study conducted 86.4% of neonates had mild thrombocytopenia while moderate and severe thrombocytopenia was seen in 14.6% of babies. 6 Our study didn't observe any significant difference in incidence of thrombocytopenia as far as gender was concerned which is comparable to the study. 5 This study observed that preterm babies who received phototherapy had significantly higher incidence of thrombocytopenia than term babies which was in comparison with the study.…”
Section: Discussionsupporting
confidence: 84%
“…This finding was in contrast to the studies; however, their results were not statistically significant. 5,6,7,8…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Another study conducted by Boskabadi et al on incidence of thrombocytopenia in idiopathic hyperbilirubinemic newborns also showed that 86.4% of babies with NNH had mild thrombocytopenia. 22 In a study conducted by Khera et al on incidence of thrombocytopenia following phototherapy in hyperbilirubinemic neonates, an association of phototherapy as a cause of thrombocytopenia in hyperbilirubinemic neonates was established. 23 Zieve et al demonstrated effects of high intensity white light on human platelets in vitro.…”
Section: Neonatal Factorsmentioning
confidence: 99%
“…The kernicterus manifests as devastating permanent brain injury leading eventually to permanent brain retardation. [3][4][5] The NH occurs because of imbalance of liver functioning due to immaturity and increased bilirubin load to detoxify. This results in lagging behind of bilirubin in capillaries giving an appearance of yellowness (jaundice).…”
Section: Introductionmentioning
confidence: 99%
“…However, many adverse effects have been reported in the medical literature. [3][4][5][6] Reported side effects of PT are; dehydration due to insensible water loss, hyperthermia, skin rash, retinal damage, loose stool, hypocalcemia, risk of patent ductus arteriosus, hypocalcemia, skin damage, and genotoxicity. 8,9 Previous human studies [8][9][10] suggested phototherapy causes the low blood platelet counts called the thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%